PENDAMPINGAN PENYUSUNAN PROGRAM PENGEMBANGAN DESA LABORATORIUM - Suripan, Suripan; Sucipto, Sucipto; Nurhadi, Nurhadi; Sopingi, Sopingi (ABDIMAS PEDAGOGI, 2017)
Abstract: The purpose of community service activity is to improve the ability of the Board of Education Social Institution (Lembaga Sosial Pendidikan / LSP) Harapan and community leaders of Gajahrejo Village to understand the social and economic problems of the rural areas and develop programs based on the potential and environmental problems by involving all local development stakeholders. The mentoring technique was conducted through Focussed Group Discussion (FGD) twice with the involvement of the management of Yayasan Sosial Pendidikan Harapan, community leaders and local village apparatus, and the PLS students who conducted the Field Experience Study program. This technique is able to provide enlightenment to the participants on how to set up a good program by involving the participation of all community representatives. The outcomes of this activity are: (1) problem and potential map (social, economic, education, geographic, cultural) and information development of community development program managed by LSP Harapan; and (2) community development plans of Gajahrejo and Sidodadi Village, which were developed in a participatory manner, describing the efforts that include the development of education, economic, environmental, and cultural programs, as well as tourism development.Keywords: mentoring, programming, laboratory villagesAbstrak: Tujuan dari kegiatan pengabdian pada masyarakat adalah untuk meningkatkan kemampuan pengurus Lembaga Sosial Pendidikan (LSP) Harapan dan tokoh masyarakat Desa Gajahrejo dalam memahami persoalan sosial ekonomi pedesaan dan mengembangkan program yang berbasis pada potensi dan masalah lingkungan dengan melibatkan segenap stakeholder pembangunan setempat. Teknik pendampingan dilakukan melalui Focussed Group Discussion (FGD) sebanyak dua kali dengan melibatkan pengurus Yayasan Sosial Pendidikan Harapan, tokoh masyarakat dan perangkat desa setempat, serta mahasiwa PLS yang melakukan program Kajian Pengalaman Lapang (KPL). Teknik ini mampu memberikan pencerahan kepada peserta tentang bagaimana menyusun program yang baik dengan melibatkan pertisipasi segenap perwakilan masyarakat. Hasil kegiatan ini adalah: (1) peta masalah dan potensi (sosial, ekonomi, pendidikan, geografis, budaya) dan informasi perkembangan program pengembangan masyarakat yang dikelola LSP Harapan; dan (2) rencana program pengembangan masyarakat Desa Gajahrejo dan Sidodadi, yang disusun secara partisipatif, yang menggambarkan upaya yang meliputi pengembangan program pendidikan, ekonomi, lingkungan, dan budaya, serta pengembangan wisata.Kata kunci: pendampingan, penyusunan program, desa laboratorium